일 지역 간호사의 임종기 치료 선호도 - 김현숙; 김신미; 유수정; 김명옥; Kim, Hyun-Sook; Kim, Shin-Mi; Yu, Su-Jeong; Kim, Moung-Ok (Han'guk Hosŭpʻisŭ Wanhwa Uiryo Hakhoe chi = The Korean journal of hospice and palliative care, 2010)
Purpose: This study was performed to explore the preference for care near the end-of-life of nurses who had been working in an acute hospital. Methods: Data were collected by using PCEOL-K which was originally developed in U.S. and standardized into Korean version. Two hundred nurses from one acute hospital who agreed to participate in the study filled out questionnaires and 177 questionnaires were analyzed for the study results. Results: Relatively positive preference toward spirituality and pain control and negative preference toward decision making by health care professional were uncovered. Conclusion: Nurses consider patient's autonomy, pain control and spirituality as important factors at the end-of-life care. Further studies regarding the preference for the care near the end-of-life of diverse groups such as patients, doctors, and family members are called for. 목적: 본 연구는 간호사들의 임종기 동안의 치료 및 간호와 관련한 간호사 자신의 선호도를 확인하기 위하여 수행되었다. 방법: PCEOL-K를 이용하여 자료를 수집하였으며 본 도구는 미국에서 개발되고 한국판 표준화를 거친 도구이다. 연구대상자는 본 연구 참여를 허락한 일 종합병원의 간호사 200명이었으며 총 177매의 자료가 분석에 활용되었다. 결과: 본 연구 대상 간호사들은 임종기 치료 및 간호에 있어 통증관리 및 영적 요구지지에 대한 긍정적 선호도를, 의료인에 의한 치료 결정에 대해서는 부정적 선호도를 나타내었다. 결론: 본 연구 결과 간호사들은 임종기 치료 및 간호에서 개인의 자율성, 통증관리, 영적 요구 지지를 중요하게 생각하고 있었다. 앞으로 다양한 집단, 즉 의사, 환자, 가족들을 대상으로 각 집단별 선호도를 확인하는 노력이 요구된다.